A roadmap for gene drives: using institutional analysis and development to frame research needs and governance in a systems context. (24th January 2018) - Kuzma, J.; Gould, F.; Brown, Z.; Collins, J.; Delborne, J.; Frow, E.; Esvelt, K.; Guston, D.; Leitschuh, C.; Oye, K.; Stauffer, S.
ABSTRACT: The deployment of gene drives is emerging as an alternative for protecting endangered species, controlling agricultural pests, and reducing vector-borne diseases. This paper reports on a workshop held in February 2016 to explore the complex intersection of political, economic, ethical, and ecological risk issues associated with gene drives. Workshop participants were encouraged to use systems thinking and mapping to describe the connections among social, policy, economic, and ecological variables as they intersect within governance systems. In this paper, we analyze the workshop transcripts and maps using the Institutional Analysis and Development (IAD) framework to categorize variables associated with gene drive governance and account for the complexities of socio-ecological systems. We discuss how the IAD framework can be used in the future to test hypotheses about how features of governance systems might lead to certain outcomes and inform the design of research programs, public engagement, and anticipatory governance of gene drives.